Sotatercept in the Treatment of Pulmonary Arterial Hypertension: A Comprehensive Narrative Review of Mechanism, Efficacy and Future Directions - Ranjan, Niroshan; Ahmed, Ahmed; Woods, Jordana; Selvaraj, Ramaneshwar; Patel, Mihir; Dalati, Yaman; Sabanathan, Vidushan; Thangadurai, Thanujan (Journal of Pulmonology and Respiratory Research, 2025)
Rationale: Pulmonary Arterial Hypertension (PAH) is a progressive vascular remodeling disease with elevated pulmonary vascular resistance that is lethal. While therapeutic progress was recently made with endothelin, nitric oxide, and prostacyclin pathway-based therapy for the treatment of PAH, the disease is currently incurable with a high cost of morbidity and mortality. Sotatercept, a new activin receptor IIA-Fc fusion protein, may prove to be a game-changer as a therapeutic agent for the treatment of PAH by regulating the growth factor signaling aberration of PAH. Methods: It is a narrative review of evidence for the drug Sotatercept for Group 1 PAH from a systematic literature search for clinical trials, mechanism studies, and regulatory data up to 2024. Pivotal clinical trials such as PULSAR, SPECTRA, STELLAR, and ZENITH were evaluated for efficacy, safety, and comparative results. Results: Sotatercept is a TGF-β family member ligand trap that rebalances activin/BMP signaling to target vascular remodeling. Clinically, striking effects were shown with exercise (40.8 m improvement in STELLAR 6MWD), pulmonary hemodynamics (PVR reduction of 146-240 dyn·s·cm-5 in PULSAR), as well as clinical measures (76% reduction of composite morbidity/mortality through ZENITH). On the background with an acceptable drug safety profile of predominantly hematologic effects, as well as injection site reaction, benefits were achieved. Comparison with analyses implies at least similar, if superior in some dimensions, efficacy of current PAH therapies. Conclusion: Sotatercept is a new therapeutic option for PAH as the first drug to act on the activin/BMP pathway. With its strong effect on several clinically relevant end points, it is a “fourth pillar” of PAH therapy. Clinical trials will determine its place in the algorithm, ascertain other combinations, and potentially identify its utility for other types of pulmonary hypertension.